2018
DOI: 10.1371/journal.pone.0191964
|View full text |Cite
|
Sign up to set email alerts
|

Subsequent somatic axis and bone tissue metabolism responses to a low-zinc diet with or without phytase inclusion in broiler chickens

Abstract: Zinc is required for normal bone development and cartilage formation. The purpose of this study was to assess the effect of with adding organic Zn (alone or phytase inclusion) at the reduced dose to growing male Ross 308 chickens on somatic axis and bone tissue metabolism. 200 one-day old broilers were divided into the negative control group fed diet without Zn or phytase inclusion, positive control group receiving Zn in the 100% of daily recommended dose from ZnO, and two experimental groups fed diet introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 63 publications
1
20
0
1
Order By: Relevance
“…Besides calcium, other minerals are present in bee pollen (Table 2). Zinc plays important roles in bone metabolism as a catalyst of many enzymes that affect mineralization, such as bone alkaline phosphatase [53][54][55][56]. While alkaline phosphatase activity was not measured in the present study, Yamaguchi et al [5] showed that dietary bee pollen can promote alkaline phosphatase activity in metaphyseal tissues of bones, which, with increased mineralization, point to enhanced remodeling of trabecular bone.…”
Section: Plos Onementioning
confidence: 52%
“…Besides calcium, other minerals are present in bee pollen (Table 2). Zinc plays important roles in bone metabolism as a catalyst of many enzymes that affect mineralization, such as bone alkaline phosphatase [53][54][55][56]. While alkaline phosphatase activity was not measured in the present study, Yamaguchi et al [5] showed that dietary bee pollen can promote alkaline phosphatase activity in metaphyseal tissues of bones, which, with increased mineralization, point to enhanced remodeling of trabecular bone.…”
Section: Plos Onementioning
confidence: 52%
“…Bone remodeling and maturation, which involves changes in bone size and shape, depend on the interaction between bone cells activities, intermolecular networks of collagen, and interactions of proteoglycans and non-collagenous proteins. Poorly designed diet may influence these processes and lead to severe skeletal disorders [3, 59].…”
Section: Introductionmentioning
confidence: 99%
“…Copper, zinc, manganese and magnesium are essential cofactors for enzymes involved in collagen synthesis and other bone matrix constituents that are required in bone and cartilage formation processes [48,49]. Thus, this enhanced mineral bioavailability may be directly related to the observed improvements in trabecular bone microarchitecture and articular cartilage histomorphometry, as has been reported in numerous previous studies on poultry, by our laboratory [50][51][52][53].…”
Section: Discussionmentioning
confidence: 53%